2018
DOI: 10.3390/jcm7080218
|View full text |Cite
|
Sign up to set email alerts
|

Primary Signet Ring Cell Carcinoma of the Prostate: A Rare Case Report

Abstract: Primary prostatic signet ring cell carcinoma is a rare form of cancer with a poor prognosis, which is generally treated with a traditional prostate adenocarcinoma therapy. This case report presents a 70-year-old diagnosed with primary prostatic signet ring cell carcinoma, treated with a combination of radiotherapy and hormone therapy and a 16 month survival without an evidence of the disease at follow up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Other less common primary sites of SRCC are the breast, pancreas, bladder, thyroid, and the lungs [6-7]. Primary SRCC of the prostate is even more rare, with roughly 60 cases reported in the literature [7]. In our patient with peritoneal carcinomatosis and rectal adhesions, a primary gastrointestinal malignancy was considered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other less common primary sites of SRCC are the breast, pancreas, bladder, thyroid, and the lungs [6-7]. Primary SRCC of the prostate is even more rare, with roughly 60 cases reported in the literature [7]. In our patient with peritoneal carcinomatosis and rectal adhesions, a primary gastrointestinal malignancy was considered.…”
Section: Discussionmentioning
confidence: 99%
“…Another unique finding, in this case, was the histologic morphology of signet ring cells in the ascitic fluid. Signet-ring cell carcinoma (SRCC) is a rare form of cancer that carries a poor prognosis and is most commonly found in the stomach and colon [6-7]. Other less common primary sites of SRCC are the breast, pancreas, bladder, thyroid, and the lungs [6-7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lilleby et al [9] presented that at 12 months after initiation of HT+RT combination therapy, one of their patients was able to control the disease without distant metastasis. Alpergok et al [10] reported that a patient who received HT+RT combined treatment also achieved a survival of 16 months without disease progression. Cheng et al [11] reported 23 PPSRCC cases which were treated with RP+HT and HT+RT.…”
Section: Discussionmentioning
confidence: 99%